Ground Deformation Assessment of the Albertine Graben Using INSAR - Otukei, J.R.; Atolerea, P.; Gidudu, A. F.Martinic (South African Journal of Geomatics, 2019)
Information on deformation of the land surface is vital for planning of infrastructure especially in areas such as the Albertine graben with substantial amounts of oil discoveries. Traditionally, global positioning systems, precise leveling and geotechnical techniques have been used for assessing and monitoring ground deformations. While these techniques provide accurate information, they are point based, expensive, time consuming and labour intensive over large area monitoring. This study explored an interferometric synthetic aperture radar (InSAR) approach for mapping deformation over Buliisa oil discovery area located in the Western arm of the East African rift valley. The method was implemented by measuring the phase differences of ALOS PALSAR data acquired between 2007 and 2011. Deformation estimates varied between -0.45m to +0.34m while the mean displacements varied from –0.10m to 0.089m. High ground deformation was detected in the Southern, North Eastern and North Western parts contributed by agricultural activity and drilling pad constructions. Generally, analysis of ALOS PALSAR data using InSAR approach provides a viable option for assessing land surface deformation in Buliisa oil exploration area.
Keywords: Deformation; INSAR; Differential interferometry